Integrative Digital Infographic Media Innovation for Islamic Religious Education-Science in Senior High School Educational Institutions in Pacitan Regency - Ismail, Ismail; Khozin, Khozin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to analyze the innovation of integrative digital infographic media in Islamic Religious Education and Science learning at the senior high school level. This research employed a qualitative method with a descriptive approach. The data consisted of primary and secondary data obtained from Islamic Religious Education teachers, Science teachers, and students involved in digital media–based learning activities at SMAN 1 Pacitan and SMAN 2 Pacitan. Data sources included informants, learning activities, and relevant documents. Data were collected through classroom observations, semi-structured interviews, and documentation. The data analysis technique used an interactive model, including data reduction, data display, and conclusion drawing. The findings reveal that the use of integrative digital infographic media improves instructional clarity, facilitates the integration of Islamic values with scientific concepts, and enhances students’ engagement and learning motivation. In addition, this media supports students in developing a holistic understanding of the relationship between Islamic teachings and scientific phenomena. Although challenges were identified, such as limited teacher technical skills and time constraints in media development, the implementation of this innovation remains feasible and effective, even in non-metropolitan school contexts. In conclusion, integrative digital infographic media represent a relevant and effective instructional innovation in supporting meaningful and contextual learning. The significance of this study lies in its contribution to the development of integrative learning theory and its practical implications for educators and policymakers in advancing digital-based instructional innovation in secondary education.